Leveraging the 2023 FIFA women`s world cup for sustainable fan engagement - a preliminary analysis - Cutrupi, C. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
The substantial long-term growth experienced by women`s football globally has recently resulted in a familiar phase of stagnation, as attendance numbers struggle to remain consistently high and broadcast demands not being met (Meier, 2020). This has also been evident in Australia where the women`s national team, the Matildas thrives while the semi-professional A League Women has struggled to grow in regards to game attendance and spectator engagement (Football Federation Australia, 2019). In this presentation, we investigate how the leveraging of a sport mega event - the 2023 FIFA Women`s World Cup - can contribute to sustainable fan engagement of women`s football in Australia. The hosting of the FIFA WWC 2023 in Australia and New Zealand in July/August 2023 presents a significant opportunity for Football Australia and its stakeholders to advance women`s sport into a position that ensures a prosperous and sustainable future. However, while we know about the leveraging intentions of event organisers to achieve economic and socially driven outcomes (Chalip & Leyns, 2002; Chalip, 2004; Chalip, 2006; D`Hoore et al., 2022) - and how significant fans are to value growth (Kolyperas & Maglaras, 2018; Allison, 2013) - we know very little about sport organisations and how they view leveraging events as a tool to achieve sustainable fan engagement (Smith, 2014; Schulenkorf et al., 2016; Singleton, 2017) - especially in women`s sport. Moreover, existing literature has indicated that much of the research conducted within the fan engagement space has primarily focused on men`s sporting teams and events, with limited data available on women`s sporting leagues (Toffoletti, 2017; Delia, 2020; Clarke et al., 2022). Taken together, there is a lamentable gap in the space of event leverage and sustainable growth in women`s sport that deserves to be examined from an organisational perspective (see Sant, 2015; Wasser et al., 2022; Dionisio et al., 2022). In this presentation, we offer preliminary findings from a larger research study on event leverage for sustainable fan engagement around the WWC 2023. Specifically, we look back at previous sport event leverage attempts and assess key strategies that have been successfully implemented by sporting organisations in their respective leveraging efforts. Moreover, we provide structured social media data that we collected in the lead-up to the event and discuss how social media can be used as a tool to maximise event-related opportunities. In doing so, we make two critical contributions across practice and theory. First, we illicit a number of socio-managerial strategies for event organisers and sport organisations to use in their leveraging efforts; and second, we propose a new event leverage framework that goes beyond current conceptualisations by focusing specifically on (sustainable) fan engagement as a core outcome.